If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7 + -6x = 9 Reorder the terms: 7 + 7x + -6x = 9 Combine like terms: 7x + -6x = 1x 7 + 1x = 9 Solving 7 + 1x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1x = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 9 + -7 1x = 9 + -7 Combine like terms: 9 + -7 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 6x^2=1296 | | -x^2+9x=20 | | 3x+2x-5=6 | | 8x^2+4x=0 | | 0=7x^2-35 | | 9x+5=6x+7 | | 2x+7=9x-6 | | 7n+4=46 | | 5-2x=3x+9 | | 8x^2-14x+9=0 | | 0.63=0.9m | | 2(4z-1)-3(z+1)-2(z+1)= | | -6(3+x)=-18 | | 8x^2+20x+3= | | 4x^2-20x+9= | | -6x-45=45 | | 8x+29=71 | | -4x-28=116 | | 30y^2-19y-5=0 | | -2x+18=56 | | 0.04x^2-8.504x+25302=0 | | 2x+17=25 | | -x-2=-4x-29 | | x^2-212.6x+632550=0 | | 6*x=3 | | -8-3x+7x=-28 | | x-8x+16=0 | | -3(2y-4)=-6 | | -9x+5x-4x=0 | | 3x+8=x+18 | | 49t^2+147t=0 | | -15=x |